ضبط كلفة مشاريع الأبنية السكنية خلال مراحل التصميم - كنجو, عماد; جراد, فايز; كيَّـال, رنيم (Latakia University Journal -Engineering Sciences Series, 2019)
يتناول هذا البحث موضوع ضبط كلفة الأعمال الرئيسية لمشاريع الأبنية السكنية خلال مرحلة التصميم. يندرج البحث ضمن إطار تنظيم المشاريع حيث تم استخدام ضبط الكلفة كأداة للمساعدة على التصميم واتخاذ القرار. تم اعتماد منهجية ضبط الكلفة من خلال دراسة مختلف الحلول الممكنة تقنياً واختيار الأنسب وفق معيار الكلفة حيث تُشكل هذه المنهجية واحدة من المنهجيات الأساسية لضبط الكلفة. تم عرض مختلف النماذج الضرورية مثل نمذجة معطيات التصميم، معطيات التنفيذ وتنظيم المشاريع للوصول إلى تصميم هيكلية قاعدة البيانات العلائقية والتي تم إغناؤها بالمعلومات التي جُمعت من مشاريع أبنية مختلفة، وأخيراً تمت برمجة القاعدة لبناء تطبيق برمجي يساعد المصممون في تقدير وضبط كلفة مشاريعهم. The topic of controlling the cost of building projects' main works during the design phase has been dealt in this research. Within projects organization field, this research aims to use cost controlling as an assistance tool for design and decision making. Cost control methodology has been adopted based on analyzing the many available alternatives and choosing the best one according to its cost, and this methodology is widely considered as one of the basic cost control approaches. Based on different models like modeling design, execution and projects organization related information, this research has been succeeded in developing a relational database that is fed by different building projects' field data. The developed database has been finally used in creating a computer program that can be used as a tool to assist designers in estimating and controlling the cost of their building projects.